Percutaneous hepatic perfusion (chemosaturation) with melphalan in patients with intrahepatic cholangiocarcinoma: European multicentre study on safety, short-term effects and survival - Marquardt, Steffen; Radeleff, Boris (European radiology, 2019)
Objectives: Cholangiocarcinoma is the second most common primary liver tumour with a poor overall prognosis. Percutaneous hepatic perfusion (PHP) is a directed therapy for primary and secondary liver malignancies, and its efficacy and safety have been shown in different entities. The purpose of this study was to prove the safety and efficacy of PHP in patients with unresectable intrahepatic cholangiocarcinoma (iCCA). Patients and methods: We retrospectively reviewed data from 15 patients with unresectable iCCA treated with PHP in nine different hospitals throughout Europe. Overall response rates (ORR) were assessed according to response evaluation criteria in solid tumours (RECIST1.1). Overall survival (OS), progression-free survival (PFS) and hepatic PFS (hPFS) were analysed using the Kaplan-Meier estimation. Adverse events (AEs) and toxicity were evaluated. Results Fifteen patients were treated with 26 PHPs. ORR was 20%, disease control was achieved in 53% after the first PHP. Median OS was 26.9 months from initial diagnosis and 7.6 months from first PHP. Median PFS and hPFS were 122 and 131 days, respectively. Patients with liver-only disease had a significantly longer median OS compared to patients with locoregional lymph node metastases (12.9 vs. 4.8 months, respectively; p < 0.01). Haematological toxicity was common, but manageable. No AEs of grade 3 or 4 occurred during the procedures. Discussion PHP is a standardised and safe procedure that provides promising response rates and survival data in patients with iCCA, especially in non-metastatic disease. Key Points: Percutaneous hepatic perfusion (PHP) offers an additional locoregional therapy strategy for the treatment of unresectable primary or secondary intrahepatic malignancies. PHP is a standardised and safe procedure that provides promising response rates and survival data in patients with intrahepatic cholangiocarcinoma (iCCA), especially in non-metastatic disease. Side effects seem to be tolerable and comparable to other systemic or local treatment strategies.